Influence of supplementary food on the behaviour of Greylag Geese Anser anser in an urban environment - Käßmann, Sonja; Woog, Friederike (Wildfowl, 2013)
Feral Greylag Geese Anser anser were studied in Stuttgart, Germany, in autumn and winter 2004/05 to determine whether the provision of supplementary food, mainly bread, affected their behavioural patterns. The birds’ activities, recorded by flockscans made at regular intervals throughout the day, were compared for days with and without supplementary food. The main activities recorded were feeding and loafing in both circumstances, but the proportion of time that the birds spent feeding was significantly lower on days when food was provided (43%) than on days when they grazed on the town’s lawns without any additional food (67%). Conversely, the amount of time that the birds spent loafing was higher on days when fed by the public (25%) than on days when they were not (14%). The difference in diurnal patterns was most evident from 13:00 h onwards, which coincided with the increase in the provision of food in the second half of the day. When supplementary food was available, vigilance behaviour also doubled from 8% to 16%, and more social interactions (mainly agonistic behaviour) and locomotion were observed.